2011
DOI: 10.3184/096034011x13061599631976
|View full text |Cite
|
Sign up to set email alerts
|

Micro mechanics based on vacancy diffusion coupled with damage mechanics related to creep deformation and prediction of creep fracture life

Abstract: In situ observations of crack growth and damage progression were conducted under creep conditions for P92 and titanium aluminides inter-metallic compound. A proposed analysis of stress induced particle diffusion was applied to stress induced vacancy diffusion. Results obtained from this analysis were successfully correlated with the experimental behaviour of macroscopic damage progression and a theoretical characteristic of creep deformation was derived. It was found to be in good agreement with experimental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 16 publications
(20 reference statements)
1
24
0
Order By: Relevance
“…The first category closely concerns fracture mechanics [15][16][17][18][19][20]. The second category closely concerns macro-scale damage mechanics [21][22][23] and the nucleation theory of voids caused by vacancy diffusion [24][25][26][27], whereas the third category relates to vacancy diffusion and the adopted method of analysis of stress induced vacancy diffusion [28]. The adopted basic equation is that of potential driven particle diffusion which was validated by many authors [29][30][31].…”
Section: The Concept Of Multi-scale Mechanical Damage Under High Tempmentioning
confidence: 99%
See 4 more Smart Citations
“…The first category closely concerns fracture mechanics [15][16][17][18][19][20]. The second category closely concerns macro-scale damage mechanics [21][22][23] and the nucleation theory of voids caused by vacancy diffusion [24][25][26][27], whereas the third category relates to vacancy diffusion and the adopted method of analysis of stress induced vacancy diffusion [28]. The adopted basic equation is that of potential driven particle diffusion which was validated by many authors [29][30][31].…”
Section: The Concept Of Multi-scale Mechanical Damage Under High Tempmentioning
confidence: 99%
“…A void is originated by nucleation mechanisms and it grows and links with other voids, which results in micro grain boundary cracks. Previous work has shown that the mechanical treatment of the damage function, ω, is different depending on the scale of each observed damage [28]. Furthermore, based on the application of experimental results obtained in laboratories to the case of actual engineering structures, the effect of local multi-axial stress on creep deformation and crack growth is involved in structural geometries of engineering structures.…”
Section: The Concept Of Multi-scale Mechanical Damage Under High Tempmentioning
confidence: 99%
See 3 more Smart Citations